Merjenje dimenzij trahej hrasta (Quercus sp.) na makroskopskem nivoju s sistemom za analizo slike - Lucia G - Merela, Maks (Les (Ljubljana), 2005)
System for image analysis Lucia G was used for measuring vessel dimensions of oak wood (Quercus sp.) on macroscopic level. We present the problem of sample preparation as well as capturing and processing of images for automatic measurements of diameters, areas and perimeters of early wood vessels. After testing various methods of sample preparation we found out that the best results were obtained when the samples were sanded with paper of granulation 320 and the surface stained with black alcohol marker. Vessel lumina were then filled with white chalk dust, and finally the images were captured by a digital camera attached to a stereo microscope and saved in TIF format. We improved the images by using digital filters, converted them to binary images and defined measurement frames. The results confirmed that the image analysis system Lucia G enables measurements of early wood vessel dimensions in ring porous species on macroscopic samples with satisfying accuracy.
Keywords: Croatian Growth; hrast; Quercus sp.; les; traheje